Keeping your options open: Maintenance of thermal plasticity during adaptation to a stable environment. (1st January 2016) - Fragata, Inês; Lopes‐Cunha, Miguel; Bárbaro, Margarida; Kellen, Bárbara; Lima, Margarida; Faria, Gonçalo S.; Seabra, Sofia G.; Santos, Mauro; Simões, Pedro; Matos, Margarida
Abstract: Phenotypic plasticity may allow species to cope with environmental variation. The study of thermal plasticity and its evolution helps understanding how populations respond to variation in temperature. In the context of climate change, it is essential to realize the impact of historical differences in the ability of populations to exhibit a plastic response to thermal variation and how it evolves during colonization of new environments. We have analyzed the real‐time evolution of thermal reaction norms of adult and juvenile traits in Drosophila subobscura populations from three locations of Europe in the laboratory. These populations were kept at a constant temperature of 18ºC, and were periodically assayed at three experimental temperatures (13ºC, 18ºC, and 23ºC). We found initial differentiation between populations in thermal plasticity as well as evolutionary convergence in the shape of reaction norms for some adult traits, but not for any of the juvenile traits. Contrary to theoretical expectations, an overall better performance of high latitude populations across temperatures in early generations was observed. Our study shows that the evolution of thermal plasticity is trait specific, and that a new stable environment did not limit the ability of populations to cope with environmental challenges.